Comparative gastrointestinal safety of weekly oral bisphosphonates - Cadarette, S. M. (2009)
SUMMARY: Weekly bisphosphonates are the primary agents used to treat osteoporosis. Although these agents are generally well tolerated, serious gastrointestinal adverse events, including hospitalization for gastrointestinal bleed, may arise. We compared the gastrointestinal safety between weekly alendronate and weekly risedronate and found no important difference between new users of these agents. INTRODUCTION: Weekly bisphosphonates are the primary agents prescribed for osteoporosis. We examined the comparative gastrointestinal safety between weekly bisphosphonates. METHODS: We studied new users of weekly alendronate and weekly risedronate from June 2002 to August 2005 among enrollees in a state-wide pharmaceutical benefit program for seniors. Our primary outcome was hospitalization for upper gastrointestinal bleed. Secondary outcomes included outpatient diagnoses for upper gastrointestinal disease, symptoms, endoscopic procedures, use of gastroprotective agents, and switching between therapies. We used Cox proportional hazard models to compare outcomes between agents within 120 days of treatment initiation, adjusting for propensity score quintiles. We also examined composite safety outcomes and stratified results by age and prior gastrointestinal history. RESULTS: A total of 10,420 new users were studied, mean age=79 years (SD, 6.9), and 95% women. We observed 31 hospitalizations for upper gastrointestinal bleed (0.91 per 100 person-years) within 120 days of treatment initiation. Adjusting for covariates, there was no difference in hospitalization for upper gastrointestinal bleed among those treated with risedronate compared with alendronate (HR, 1.12; 95%CI, 0.55 to 2.28). Risedronate switching rates were lower; otherwise, no differences were observed for secondary or composite outcomes. CONCLUSIONS: We found no important difference in gastrointestinal safety between weekly oral bisphosphonates.